Recent advances in experimental studies of social dilemma games - Ananish Chaudhuri (Games, 2016)
I provide a broad overview of the findings reported in the articles submitted for this special volume on experimental studies of social dilemma problems. I start by providing a synopsis of where current research stands on this topic. Then I go on to discuss the specific papers and how those papers extend our knowledge in this area and add value to the current state of the art.
Keywords: 330; experiments; social dilemma games; voluntary contributions; public goods; common pool resource extraction